Current water quality status at compartment 13 waterfall in Ayer Hitam Forest Reserve, Puchong Selangor - Ahmad, Arif Asnami (2018)
Ayer Hitam Forest Reserve (AHFR) is a secondary forest which has logging operation history. Logging activities have caused deterioration in Water Quality Index (WQI) in the forest. A study was carried out at the waterfall in AHFR, Puchong Selangor. The main objective of this study was to determine the current water quality status at Waterfall in AHFR by using DOE-WQI index with six water quality parameters that are Dissolved Oxygen (DO), pH, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonia-cal Nitrogen (NH3N) and Total Suspended Solid (TSS). The study involved four stations along from the upper stream to the lower stream. Station 1 was located at the cliff of the upper stream, followed by Station 2 and 3 was located at middle stream which Station 3 is the second cliff on the middle stream and Station 4 at the river branch of the waterfall where the river was connected with Sungai Rasau. The sampling was conducted once a week in the period of six weeks. One Way Analysis of Variance (ANOVA) was used to make comparisons of parameters and WQI among stations. WQI result showed the range of mean value was from 79.15 to 86.46 and p value was 0.54 which means that was no significant differences among stations. The water quality status at the waterfall in AHFR Puchong, Selangor is under class II which indicates it suitability for recreational activities but provided water is being implemented.